Sistem Informasi Pemasaran Produk Batik Di Rama Mukti Solo Berbasis Web - Alfian Alief Nurrohman; Azizah Fatmawati (Jurnal Media Computer Science, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a very important role in the Indonesian economy. Not only do they create jobs, but they also contribute to inclusive economic growth. There many types of MSMEs in Indonesia, with batik businesses being among the more prominent. Batik Rama Mukti still faces obstacles in product marketing, specifically relying on manual sales through offline stores and lacking awareness about benefits of digital marketing. This study aims to build an information system Batik Rama Mukti’s product marketing to support the development of a digital MSME. The research methodology uses the software development life cycle with the waterfall method, which includes several stages: requirements analysis, system design, implementation, testing, and maintenance. This system is also built using the PHP programming language with the Laravel framework and database management with MySQL. Additionally, Black Box testing and the System Usability Scale (SUS) are conducted. Based on the Black Box testing, the system is functioning well and as expected. The SUS testing resulted in a score of 78.9, which falls into the good category. The results of this information system can facilitate both buyers and administrators in accessing it.